Identification of new benzimidazole-triazole hybrids as anticancer agents: multi-target recognition, in vitro and in silico studies - Dina I. A. Othman; Abdelrahman Hamdi; Samar S. Tawfik; Abdullah A. Elgazar; Amany S. Mostafa (Taylor & Francis Group, 2023)
Multi-target inhibitors represent useful anticancer agents with superior therapeutic attributes. Here in, two novel series of benzimidazole-triazole hybrids were designed, synthesised as multi-target EGFR, VEGFR-2 and Topo II inhibitors, and evaluated for anticancer activity. Compounds 5a and 6g were the most potent analogues against four cancer cell lines, HepG-2, HCT-116, MCF-7 and HeLa, and were further evaluated for EGFR, VEGFR-2, and Topo II inhibition. Compound 5a was especially good inhibitor for EGFR (IC50 = 0.086 µM) compared to Gefitinib (IC50 = 0.052 µM), moderate VEGFR-2 inhibitor (IC50 = 0.107 µM) compared to Sorafenib (IC50 = 0.0482 µM), and stronger Topo II inhibitor (IC50 = 2.52 µM) than Doxorubicin (IC50 = 3.62 µM). Compound 6g exhibited moderate EGFR and VEGFR-2 inhibition and weaker Topo II inhibition. DNA binding assay, cell cycle analysis, apoptotic induction, molecular docking, and physicochemical studies were additionally implemented to explore the plausible mechanism of the active compounds.